DOES EXPERIENTIAL DIGITAL STORYTELLING HELP PRE-SERVICE TEACHERS LEARN DIGITAL LITERACIES IN INDONESIA? - Zulikhatin Nuroh, Ermawati; Liansari, Vevy (Antis-Publisher, 2024)
Objective: This study aims to document the practices of preservice English teachers (PSETs) in integrating digital storytelling (DST) during their teaching practicum. It seeks to identify challenges, opportunities, and the pedagogical knowledge required to utilize DST effectively in English language teaching. Method: The study involved three preservice English teachers who implemented DST projects in three public secondary schools in Indonesia. Data collection was conducted through observation and interviews. The data were analyzed using thematic content analysis to explore technical, pedagogical, and practical aspects of DST integration. Results: The findings highlight three key areas: (1) Technical challenges associated with software design and use, (2) Opportunities and challenges in utilizing DST as a teaching partner, (3) The pedagogical content knowledge necessary for effective DST integration. The results suggest that equipping preservice teachers with DST knowledge and providing scaffolding can enhance the effectiveness of teaching practices. Novelty: This study contributes to the limited body of research on integrating DST in English language teaching in the Indonesian context. It emphasizes the need for further studies to evaluate the impact of English teacher education on learning outcomes and recommends developing educational programs that focus on DST.